Educación financiera y cultura tributaria en trabajadores de la empresa Corporación Vasquez e Hijos SAC, Iquitos – año 2021 - Cobos Arimuya, Rosa Milagros (2023)
The present research work entitled "Financial Education and Tax Culture in Workers of the Company Corporación Vásquez e Hijos SAC, Iquitos - year 2021" was carried out with the objective of determining what is the level of Financial Education and Tax Culture in workers of the Company Corporación Vásquez e Hijos SAC, Iquitos - year 2021, for which a descriptive investigation of a non-experimental design was chosen, where the 15 workers named from the Company Corporación Vásquez e Hijos SAC were taken as the study population and who wanted to voluntarily participate in this research work, to which the survey technique was applied and the questionnaire as an instrument; According to the analysis of the results, it was determined that 68.1% of the workers of the company Corporación Vásquez e Hijos S.A.C. they have a medium level on Financial Education and 31.9% have a low level on Financial Education, in terms of Tax Culture it was determined that 65.5% have a medium level and 34.5% have a low level, so it is concluded that the workers of the company Corporación Vásquez e Hijos have a medium level of Financial Education and Tax Culture.